Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SDN 6 Cakranegara Tahun Pelajaran 2022/2023 - Shaumy, Rizki Lolina; Herawati, Sri; Hariana, Siti Rohana; Yuliati, Ni Nyoman (Journal of Science Instruction and Technology, 2023)
This classroom action research aims to improve social studies learning outcomes for SDN 6 Cakranegara grade IV students, which is conducted collaboratively through the use of a project-based learning model (project-based learning). The subject of the study was 31 fourth grade students, and the object of the study was the learning outcomes of the students. The results of the study show that there is an increase in social studies learning outcomes among students of class IV SDN 6 Chakranegara through the use of the Project Based Learning model. The data collection method in this study is based on tests and observations. The increase in learning outcomes can be judged by the increase in student learning outcomes, student activity in class and the completeness of student learning outcomes, which increased to 80.65%. Before the start of the action, the graduation rate of students was only 29.03%, increased in Cycle I to 48.39% and continued to increase in Cycle II to 80.65%. Since the completion criteria were achieved with 75% of students achieving a score greater than or equal to KKM (75), this study is considered a success.